Quinceañera Style Social Belonging and Latinx Consumer Identities - González, Rachel Valentina (University of Texas Press, 2021)
Quinceañera celebrations, which recognize a girl's transition to young womanhood at age fifteen, are practiced in Latinx communities throughout the Americas. But in the consumer-driven United States, the ritual has evolved from a largely religious ceremony to an elaborate party where social status takes center stage. Examining the many facets of this contemporary debut experience, Quinceañera Style reports on ethnographic fieldwork in California, Texas, the Midwest, and Mexico City to reveal a complex, compelling story. Along the way, we meet a self-identified transwoman who uses the quinceañera as an intellectual space in her activist performance art. We explore the economic empowerment of women who own barrio boutiques specializing in the quinceañera's many accessories and made-in-China gowns. And, of course, we meet teens themselves, including a vlogger whose quince-planning tips have made her an online sensation. Disrupting assumptions, such as the belief that Latino communities in the United States can't desire upward mobility without abandoning ethnoracial cultural legacies, Quinceañera Style also underscores the performative nature of class and the process of constructing a self in the public, digital sphere